Factors in Teenagers' Decision Making to Become Punk - Aprinal Syah, Anggi; Sugiarto, Arridho; Nurbaniyah, Nurbaniyah (International Journal of Social Science, Education, Communication and Economics, 2024)
Salusu (1996:47) defines decision-making as the process of choosing an alternative way of acting using an efficient method according to the situation. Adolescence, derived from the Latin word "adolescens," means growing or maturing into adulthood. This stage encompasses various dimensions, including mental, emotional, social, and physical maturity (Hurlock, 1980:206). Punk, as an ideology of rebellion and anti-establishment, encompasses diverse characteristics among its members, allowing a group to secure its identity and the unique traits of the punk community. In "Philosophy of Punk," Craig O'Hara (in Aini, 2010:26) mentions three definitions of Punk. This research aims to explore the decision-making processes and identity formation within the punk community. Utilizing a descriptive survey method with a quantitative approach, data were collected through an open-ended questionnaire. The technique of data analysis involved categorizing the respondents' answers, assigning numerical codes, and then entering them into a codebook. The findings revealed that punk community members rely on collective decision-making and shared values to reinforce their identity. This research provides valuable insights into the dynamics of adolescence and subcultural identity, contributing to a broader understanding of youth cultures.